Characterization of the two-protein complex in Escherichia coli responsible for lipopolysaccharide assembly at the outer membrane - Chng, Shu-Sin (National Academy of Sciences, 2010)
Lipopolysaccharide (LPS) is the major glycolipid that is present in the outer membranes (OMs) of most Gram-negative bacteria. LPS molecules are assembled with divalent metal cations in the outer leaflet of the OM to form an impervious layer that prevents toxic compounds from entering the cell. For most Gram-negative bacteria, LPS is essential for growth. In Escherichia coli, eight essential proteins have been identified to function in the proper assembly of LPS following its biosynthesis. This assembly process involves release of LPS from the inner membrane (IM), transport across the periplasm, and insertion into the outer leaflet of the OM. Here, we describe the biochemical characterization of the two-protein complex consisting of LptD and LptE that is responsible for the assembly of LPS at the cell surface. We can overexpress and purify LptD and LptE as a stable complex in a 1∶1 stoichiometry. LptD contains a soluble N-terminal domain and a C-terminal transmembrane domain. LptE stabilizes LptD by interacting strongly with the C-terminal domain of LptD. We also demonstrate that LptE binds LPS specifically and may serve as a substrate recognition site at the OM.